Synthesis, Morphology And Superconductingproperty Characterization Of Mgxb2 And Mgb2 With Sib4 Additions - Mohd Aris, Mohd Faisal (2009)

(untitled)
This project deals with the processing of MgB2 bulk samples and the effect of addition of SiB4. The correlation between fabrication parameters and superconducting properties was studied. MgB2 bulks were prepared by a pellet-inclosed- tube (PICT) and solid-state reaction route methods. MgB2 bulk samples were prepared at different annealing temperatures of 650°C, 700°C, 750°C and 800°C. AC susceptibility measurements showed a sharp superconducting transition in all the samples. However, MgB2, samples annealed at 650°C showed slightly low volume susceptibility compared to other samples. The critical current density (Jc) was measured using ac magnetic susceptibility measurement method. The highest critical density in magnetic field, Jc(T,H) from the magnetization measurements was recorded at 3.0×104A/cm2 (5K, 6T) and 7.0×103 A/cm2 (20K, 4T) for the 650°C annealed MgB2. X-ray diffraction (XRD) analysis showed small quantities of MgO and unreacted Mg phases as impurities in the samples. The second part of the work concentrates on Mg non-stoichiometry in MgxB2 (x = 0.8, 1.0 and 1.2) samples. The critical temperature (Tc), was significantly reduced in sample x = 0.8 and x = 1.2 as compared to sample with x=1.0. The Mg0.8B2 sample shows the highest Jc at 5K and 20K, followed by Mg1.2B2 and MgB2 samples, respectively. MgB2 shows the lowest Jc for all temperatures.